Type 3 macular neovascularization in a patient with pentosan polysulfate maculopathy - Elodie Bousquet; Brian A. Lee; Ahmad Santina; SriniVas Sadda; David Sarraf (American Journal of Ophthalmology Case Reports, 2023)
Purpose: To report the development of type 3 macular neovascularization (MNV) in a patient with pentosan polysulfate sodium (PPS) maculopathy one year after PPS cessation. Observation: A 72-year-old woman presented for decreased visual acuity in the left eye. Medical history was significant for interstitial cystitis treated with PPS for 11 years (cumulative dose of 1205 g) and PPS maculopathy. PPS was discontinued 1 year prior to presentation. Blue-light fundus autofluorescence and spectral domain optical coherence tomography confirmed the diagnosis of bilateral PPS maculopathy. OCT-angiography illustrated the development of type 3 MNV with intraretinal fluid in the left eye. Intravitreal injections of aflibercept were initiated with a good visual and anatomical response. Conclusion and importance: This report describes the development of type 3 MNV in a patient with PPS macular toxicity one year after PPS cessation. This complication emphasizes the need for regular retinal surveillance even after discontinuation of the inciting drug.